Evaluation of antioxidant, antibacterial and antidiabetic activities of different parts of Litsea polyantha extracts - Bhattarai, Sumana; Sharma, Khaga Raj (Scientific World, 2024)
The genus Litsea consists of about 700 species of evergreen trees or shrubs and is widely distributed in tropical and subtropical countries of the world. Litsea polyantha is used in traditional medicine around the world to cure a variety of illnesses such as influenza, diarrhea, stomach aches, diabetes, vomiting, and central nervous system. The antioxidant, antibacterial, and antihyperglycemic activity of Litsea polyantha were investigated. The antioxidant activity was performed by DPPH (2, 2-diphenyl-1-picrylhydrazyl) assay, and hyperglycemic activity was performed by α-amylase inhibition. The toxicity of plant extracts was assessed by brine shrimp lethality assay (BSLA) using Artemia salina as a biological test organism. The total phenolic content was found high in bark extract 182.49 ± 8.18 mg GAE/g and the total flavonoid content was found maximum in the same bark extract 71.23±2.68 mg QE/g. Bark extract and leaf extract showed the highest DPPH radical scavenging activity with an IC50 of 36.06±2.94 μg/mL and 20.46±1.05 μg/mL. For a methanolic extract of bark, ZOI was observed as 14±0.58 mm, 13±3.18 mm, and 11±0.33 mm against Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae. Similarly, for leaf, root, and stem extract ZOI was observed 10 ± 0.57 mm, 11 ± 0.67 mm, and 9 ± 0.58 mm against Staphylococcus aureus, E. Coli, and Bacillus subtilis. Bark extract and leaf extract had IC50 of 0.72±0.03 mg/mL and 2.40±0.02 mg/mL respectively. The LC50 of 835.35 μg/mL for the root extract of Litsea polyantha was shown to be toxic against brine shrimp. This study showed the different parts of Litsea polyantha are rich sources of phenolic and flavonoid content and the potential natural antioxidant and antidiabetic compounds that could be isolated